INTEGRATIV YONDASHUV ASOSIDA O‘QUVCHILARNING O‘QISH-BILISH FAOLLIGINI RIVOJLANTIRISH - Annayeva, M.R. (SCIENCE and SOCIETY, 2024)
This article is devoted to teaching methods based on integrative approaches to educational and cognitive activities of primary school students, using methods that help students master skills such as communication and critical thinking, based on various methods and student projects. In addition, the necessary skills, competencies and recommendations were discussed for applying the acquired knowledge through hands-on learning to prepare students for today's future professions.
Keywords: integrative education; pedagogical technology; competence; synthesis; interdisciplinary projects; "Student-public affairs" project; "Reflective journals or portfolio" project